Microbial and Inflammatory Salivary Biomarkers of Periodontal Diseases - Sha, Aram Mohammed; Abdulbaqi , Hayder Raad; Bin Qasim, Syed Saad (Kurdistan Journal of Applied Research, 2024)
Recent data reveals that severe periodontal diseases affect approximately 19% of global adult populations, impacting more than 1 billion individuals universally, ranking it as the sixth most predominant human disease. Diagnosis and treatment plans for periodontal disease entirely depend solely on the assessment of traditional clinical parameters. However, these parameters are not sensitive and are subject to error. Hence, microbial and inflammatory biomarkers of periodontal diseases in saliva have attracted of interest. This review aims to evaluate the salivary components as potential diagnostic tools for periodontal diseases. In addition to periodontal pathogens, interest in salivary biomarkers of periodontal disease is increasing, and a number of biomarkers have the potential to be accurate indicators of disease and the effectiveness of therapy. The most up to date studies examining the microbial and inflammatory biomarkers with both diagnostic and prognostic values in saliva were reviewed for the purpose of this study. It is apparent that saliva has many advantages over other oral fluids such gingival crevicular fluid and mouth rinse as a tool for diagnosis of periodontal disease. Biomarkers can identify and quantify periodontal risk through objective measures. Further, the combination of biomarkers seems to enhance the diagnostic and prognostic value of the biomarkers. Amongst the microbial biomarkers of Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans and Tannerella forsythia are widely used with some promising results. Whereas, the inflammatory salivary biomarkers of IL-1β and MMP-8 are widely used for diagnosing periodontitis and predicting the future treatment outcome.